The interpretation of ABET placement tests in the recognition of prior learning - Blunt, Sandra Viki (Rhodes University, Faculty of Education, Department of Education, 2000)
This thesis analyses the way in which placement testing is being interpreted in Adult Basic Education and Training (ABET). The thesis examines whether the placement tests used in the case study were valid in terms of whether their contents were relevant and authentic with regard to what English second language speakers could reasonably be expected to know. Adult learners have differing English second language knowledge depending on the different contexts in which they have learned their second language. This thesis investigates the implications of the different contexts and different language needs of adult learners for the testing of English as a second language for placement purposes in ABET programmes. The thesis examined two placement tests to determine how the recognition of prior second language learning was being interpreted and how the interpretation affected the validity of the tests. Learners= perceptions of the assessment process and test content were elicited in order to determine whether a policy of transparency had been followed in the implementation of the assessment. It was also established what the goals of the organisation were in implementing an ABET programme. This research suggests that placement testing should be viewed holistically; in other words, the goals of the organisation and the level of transparency affect the validity of the placement test. The conclusions were that the placement tests were inauthentic since their contents excluded certain vital aspects of real life performance, namely, that related to the work context. The research revealed that if the placement testing process and the ABET programme are integrated into the culture of the organisation and if employees are remunerated when they have passed the different levels in the programme, the programme is likely to achieve a fair measure of success. Recommendations are that literacy should be viewed as based on a variety of contexts and uses and that therefore tests should be tailored to suit each particular organisation and should contain workrelated content. Furthermore, multiple methods of assessment should be considered.
Keywords: English language -- Ability testing; English language -- Study and teaching -- Foreign speakers